3D modelling of rehabilitation corset with use of powershape delcam - Носов, Павло Сергійович; Яланський, Андрій Дмитрович; Яковенко, Володимир Олександрович (Eastern-European Journal of Enterprise Technologies, 2013)
Scoliosis begins in childhood or early adolescence and develops gradually with growth of the organism. After growth is finished the curvature of the spine still remains. Corsets have undergone several changes over the years in shapes and sizes, materials used, etc. However, the principle of operation remained unchanged. To improve the results of prevention and treatment corsets have to expand their opportunities to create a new generation of computerized corsets that will maximize efficiency and versatility, affordability and will allow ability to influence the individual patient model. The first step in the creation of design of a corset is the creation of a 3D model segment in the program of automated design Delcam Powershape. The design must correspond to all the above requirements: small size, strength and large internal amount, modification, fixation of a body. The basis for the future is solid cast metal construction, in which all sensors and modules are installed. The design consists of bonded segments, being able to move in all three planes of space with the help of articulated fasteners. This model offers a new approach to the diagnosis and treatment of human posture. Versatility and ease of use makes it accessible, and ability to modify and improve methods allow you to create new and innovative courses of treatments